Simulasi Degradasi Sampah Organik untuk Optimasi Siklus Penggunaan Sebuah Zona Penimbunan di TPAS Talangagung (Jurnal Ilmiah Teknologi Informasi Asia, 2017)
Increasing the waste volume is proportional to the increase in consumption and the increase of Malang residents who average of 0.73 percent every year. The data shows that there is a 150% increase in waste volume in 2015 in TPAS Talangagung. Zone 1 TPAS Talangagung as a landfill zone managed by sanitary landfill method with a capacity of 59,500 M3. Modeling and simulation are done by using system dynamics approach. The simulation results show that the accumulation of waste in 2015 and 2016 exceeds the capacity of zones by 7 percent that can be moved in other landfill zones. The predicted results in the development of validated models indicate that the results of accumulated waste in 2021 and 2022 have exceeded the zone capacity up to 201.9%. This suggests that waste management for the year requires two zones of 0.7 ha. Waste on landfill should be kept for about 4 to 7 months to degrade organic waste into compost. The composted waste can be used for agriculture and the zones can be filled with new organic waste.